India and the World Bank : the politics of aid and influence - Kirk, Jason A. (London : Anthem Press, 2010)
'The World Bank needs India more than India needs it.' So goes an emerging consensus on both sides of the relationship between the Bank and its largest borrower. This book analyzes the politics of aid and influence, with a particular focus on sub-national state-level reforms in India.
Chapter 1: Introduction: Understanding the Bond between the Bank and its Largest Borrower -- Chapter 2: The First Half-Century: From Bretton Woods to India's Reform Era -- Chapter 3: Remaining Relevant: The Bank's Strategy for an India of States -- Chapter 4: Reasserting Central Government Control, Reorienting Aid Toward 'Lagging States' -- Chapter 5: A Bittersweet Graduation: Can IDA Hold on to India, and Will India Let It? -- Chapter 6: India's Changing Relationship to Global Development Assistance.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: World Bank -- India; Loans, Foreign -- India; Economic assistance -- India; India -- Economic conditions -- 1991-